(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
Geomagnetic storms are space weather phenomena characterized by abrupt disturbances in the Earth’s magnetic field caused by solar activity. Recent scientific studies indicate that geomagnetic activity may exert a significant influence on the human body, particularly on the cardiovascular system. This literature review is devoted to the epidemiological analysis of the relationship between geomagnetic storms and attacks of arterial hypertension. The study evaluates changes in arterial blood pressure and the risk of cardiovascular complications during periods of geomagnetic activity based on modern scientific publications, meta-analyses, and epidemiological observations. According to the analyzed data, periods of geomagnetic storms may be associated with increased average blood pressure levels, decreased heart rate variability, and a higher incidence of hypertensive attacks. Therefore, the development of preventive strategies based on space weather monitoring may play an important role in reducing the risk of cardiovascular diseases.